Genome‐wide survey of artificial mutations induced by ethyl methanesulfonate and gamma rays in tomato. Issue 1 (16th February 2015) - Shirasawa, Kenta; Hirakawa, Hideki; Nunome, Tsukasa; Tabata, Satoshi; Isobe, Sachiko
Summary: Genome‐wide mutations induced by ethyl methanesulfonate (EMS) and gamma irradiation in the tomato Micro‐Tom genome were identified by a whole‐genome shotgun sequencing analysis to estimate the spectrum and distribution of whole‐genome DNA mutations and the frequency of deleterious mutations. A total of ~370 Gb of paired‐end reads for four EMS‐induced mutants and three gamma‐ray‐irradiated lines as well as a wild‐type line were obtained by next‐generation sequencing technology. Using bioinformatics analyses, we identified 5920 induced single nucleotide variations and insertion/deletion (indel) mutations. The predominant mutations in the EMS mutants were C/G to T/A transitions, while in the gamma‐ray mutants, C/G to T/A transitions, A/T to T/A transversions, A/T to G/C transitions and deletion mutations were equally common. Biases in the base composition flanking mutations differed between the mutagenesis types. Regarding the effects of the mutations on gene function, >90% of the mutations were located in intergenic regions, and only 0.2% were deleterious. In addition, we detected 1 140 687 spontaneous single nucleotide polymorphisms and indel polymorphisms in wild‐type Micro‐Tom lines. We also found copy number variation, deletions and insertions of chromosomal segments in both the mutant and wild‐type lines. The results provide helpful information not only for mutation research, but also for mutant screening methodology with reverse‐genetic approaches.